DEGRADASI MORAL DI KALANGAN PEMUKA AGAMA - Erni, Erni; Asror, Muhamad Alim Ka’batul (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This paper aims to reveal the factors causing the decline in morals among religious leaders. The type of research is a literature review using a phenomenological approach by analyzing data from news related to sexual violence in religious leaders. The study results are one, lack of understanding of religion is the most critical factor, and morals are born from religion; this happens because if someone is religious and applies religion well, of course, they have good morals. Understanding religion with its origin with radical thoughts will cause problems in society. If the religious perspective is wrong from the beginning, then it will undoubtedly take action according to its own will without thinking about the impact on others. The community focuses more on religious studies from text references without seeing the scientific source. Second, having a low level of emotional intelligence so that even though you already have total religious values, if you control yourself at a low level, there will be a desire to commit irresponsible acts, violence, and harassment.